In the shadows of Mazagan: the medina of Azamour, Morocco - Sarmento, João Carlos Vicente (2011)
This chapter focuses primarily on the material and imagined geographies of the medina of Azamour, a relatively small city in Western Morocco. The rationale behind this choice is the fact that the city – medina, literally meaning city, is generally the older part of an Arab or Muslim city – was occupied and strongly modified by the Portuguese between 1513 and 1542. I will begin by locating the trajectory of historical cities in Morocco in the discussion of Orientalism, and its significance in the construction of imagined geographies of the ‘other’, in the fascination that medinas hold for western eyes and in the recent boom of a luxury tourism based on a colonial present. I then trace the development of Azamour, briefly sketching its social and economic decline, and highlighting what seems to me the ambiguous presence and absence of its Portuguese heritage. After pointing to some experiences of tourists in Azamour, I attempt to establish a brief dialogue between the Portuguese and Arabic heritage legacy of this urban settlement and El Jadida, a much larger and important coastal city, located about 15 kilometres to the south, and principally with the recently open Mazagan Resort, seen by many as having the potential to change Azamour’s sleepy character, producing substantial changes in visitor numbers, real estate prices, employment, and so on, within the context of a contemporary tourism shift in Morocco.